Effect of intermittent fasting on obesity and metabolic indices in patients with metabolic syndrome: a systematic review and meta analysis - Shengxuan Zhang; Bixuan Sun; Lei Sun; Shijian Zou; Qilan Chen (BMC Endocrine Disorders)
Abstract Objective Dietary patterns play a vital role in the health management of individuals with metabolic syndrome. Many recent studies have shown that intermittent fasting (IF) has better effects, such as improving obesity. Nevertheless, it warrants further investigation to determine which approach is more effective in comparison to continuous energy restriction (CR), particularly when total calorie intake shows minimal variation. Consequently, it is crucial to evaluate the degree of enhancement of the two dietary patterns concerning different aspects of metabolic syndrome. This study presents a meta-analysis of randomized controlled trials (RCTs) aimed at comparing the impacts of IF and CR on obesity and glucolipid metabolism in individuals diagnosed with metabolic syndrome. Methods In August 2024, a thorough examination of English-language literature was performed across the PubMed, Medline, Embase, and Cochrane Library databases. The meta-analyses was performed according to the established guidelines and reported the results. Weight change, Body Mass Index (BMI) change, and triglyceride (TG) level change were designated as key assessment indicators, while blood pressure, blood glucose, hip circumference, and waist circumference served as supplementary indicators for comparative analysis. Result A total of nine studies involving 626 patients were analyzed, focusing on the influence of dietary patterns on obesity, cholesterol levels, and insulin resistance among individuals diagnosed with metabolic syndrome. Both dietary patterns were beneficial for patients with metabolic syndrome. However, IF was better than CRin terms of improvement in obesity over the trial period (mean -1.77, 95% CI [-3.06, -0.48]), and it was more conducive to a reduction in TG levels, which was beneficial in terms of improving insulin resistance (mean -10.16, 95% CI [-18.88, -1.45]). Conclusion Given its notable advantages for obesity, lipids, and insulin resistance, along with improved patient adherence, IF may be regarded as a more effective dietary approach for individuals with metabolic syndrome. Nonetheless, the long-term effectiveness still necessitates additional validation. Prospero registration CRD42024587335.